Applying the city development index (CDI) to measure the quality of life of the local municipalities in the northern Cape between 2001 and 2011 - Kruger, Christa Jacoba (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.